2010
DOI: 10.1016/j.bandl.2010.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Mind in adults with right hemisphere damage: What’s the story?

Abstract: a b s t r a c tWhy do people with right hemisphere damage (RHD) have difficulty with pragmatics and communication? One hypothesis has been that pragmatic impairment in RHD is the result of an underlying impairment in Theory of Mind (ToM): the ability to infer the mental states of others. In previous studies evaluating ToM abilities in people with RHD, researchers have used judgment tasks based on story or still cartoon stimuli. However, ToM is likely to draw on kinetic information as well, and these tasks igno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 62 publications
3
38
0
1
Order By: Relevance
“…Similarly, participants with RBD judged tangential conversation as normal significantly more often than NBD participants, indicating that the former may suffer from a breakdown in those components of their mental models which deal with judging intention and appropriateness in conversation . This impairment relates to the "theory of mind" explanation of their difficulties which has received some experimental support (Griffin et al, 2006;Weed, 2008;Weed, McGregor, Feldbaek Nielsen, Roepstorff, & Frith, 2010), but the theory of mind deficit in this population has been shown to be less extensive (ChampagneLavau & Joanette, 2009;Tompkins, Scharp, Fassbinder, Meigh, & Armstrong, 2006;Tompkins, Scharp, Fassbinder, Meigh, & Armstrong, 2008).…”
Section: A Model-based Theory Of Rbd Discourse Impairmentsmentioning
confidence: 95%
“…Similarly, participants with RBD judged tangential conversation as normal significantly more often than NBD participants, indicating that the former may suffer from a breakdown in those components of their mental models which deal with judging intention and appropriateness in conversation . This impairment relates to the "theory of mind" explanation of their difficulties which has received some experimental support (Griffin et al, 2006;Weed, 2008;Weed, McGregor, Feldbaek Nielsen, Roepstorff, & Frith, 2010), but the theory of mind deficit in this population has been shown to be less extensive (ChampagneLavau & Joanette, 2009;Tompkins, Scharp, Fassbinder, Meigh, & Armstrong, 2006;Tompkins, Scharp, Fassbinder, Meigh, & Armstrong, 2008).…”
Section: A Model-based Theory Of Rbd Discourse Impairmentsmentioning
confidence: 95%
“…Although both left and right pSTS and pSTG seem to be important for these functions (Saygin, 2007), some evidence suggests that the right pSTS and pSTG are particularly responsive in this sort of task (Grossman et al, 2000;Saxe, Xiao, Kovacs, Perrett, & Kanwisher, 2004). We have previously found impairment in people with RHD on a mental-state attribution task based on assessment of motion cues (Weed, McGregor, Feldbaek Nielsen, Roepstorff, & Frith, 2010). Some people with RHD may therefore be impacted in their ability to make accurate pragmatic judgements because of a reduced ability to read the motion cues of their interlocutor.…”
Section: Visual Perception and Pragmaticsmentioning
confidence: 93%
“…It has been suggested that the TPJ is selectively recruited during theory-ofmind tasks, especially during tasks that require constructing a model of someone else's beliefs (Saxe & Kanwisher, 2003;Saxe & Wexler, 2005). Damage to the TPJ is associated with impairment in theory-ofmind reasoning Samson et al, 2004;Weed, McGregor, Feldbaek Nielsen, Roepstorff, & Frith, 2010).…”
Section: Machinery For Social Perception and Cognitionmentioning
confidence: 99%